Technology, institutions and allocation of time in Swedish households 1920 - 1990 - Lars Svensson (Institute for Labour Market Policy Evaluation (IFAU), 2008)
The modernisation of Swedish households during the twentieth century prompted a considerable productivity growth in household production, which reduced the time input for a fixed volume of routine household work by about 35 per cent 1920-1990. Much of that time was gradually transferred to the labour market, but no evidence can be found for an increase in leisure time. What has been termed a Cowan paradox appears in the Swedish data: the output of household services increased significantly with productivity-enhancing technical change. This was, however, the case only in households where small children constituted an impediment to labour market entry. Increased returns to market work induced women who did not face this restriction to allocate more time to the labour market from the mid-1940s. A set of new formal and informal institutions associated with the family eventually redefined the concept of small children and so shifted the position of homemaker from being a more or less permanent status of some women to a clearly temporary position of most women.
Keywords: J22; N34; O33; 330; Time allocation; labour supply; household technologies; family policy; Haushaltsproduktion; Zeitallokation; Familienpolitik; Arbeitsangebot; Schweden